PKM SOSIALISASI DIGITAL MARKETING DAN PENGEMBANGAN WEB UMKM PANCALANG: STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT KECAMATAN PANCALANG KABUPATEN KUNINGAN - Ravindra Safitra Hidayat; Yuphi Handoko Suparmoko; Geri Suratno (Jurnal Padamu Negeri, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PKM) aims to enhance digital literacy and online marketing capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Pancalang District, Kuningan Regency, West Java. The majority of local business actors still rely on conventional marketing methods with limited market reach, and fewer than 25% have active business accounts on digital platforms. The main challenges include low levels of digital literacy, weak promotional strategies, and the absence of structured product information systems. To address these issues, the PKM team conducted awareness sessions on the importance of digital marketing, provided technical training on creating business accounts and promotional content using social media, marketplaces, and design applications (Canva), and developed a web-based MSME information website for Pancalang using web programming technologies (PHP, HTML, CSS, and JavaScript) as a digital showcase for local products. The website features menus for MSMEs, product listings, village locations, MSME activities, and contact information, enabling easier access to information for consumers. The results indicate an 80% increase in participants’ understanding, the establishment of 10 active business accounts, and the creation of an integrated digital platform for MSME promotion. Evaluation through pre-test and post-test assessments shows an improvement in participants’ digital marketing skills of 85.33%, with a potential minimum increase in revenue of 15%. The program also led to the formation of the Pancalang Digital Marketing Community (KDMP) as a sustainable collaborative forum. The Pancalang MSME website has proven effective as a practical and sustainable digital information solution, supporting the digital economic transformation of rural communities.